ANALYSIS OF WEBSITE-BASED PHYSICS LEARNING MEDIA DEVELOPMENT ON STUDENTS' PHYSICS LEARNING INTEREST - Haryadi, Rudi; Fauziah, Annida (Universitas Negeri Medan, 2024)
This study aims to analyze physics learning media's development using the website on students' interest in learning physics during the pandemic. The research method used is the literature study research method. This research method is carried out by collecting relevant data from various reading sources in the form of books, journals, and other reading sources that can support researchers in solving the subject matter under study. This study indicates that the physics learning media that has been developed based on a website can increase interest in learning physics.Keywords: Learning Media, Physics, Learning InterestThis study aims to analyze physics learning media's development using the website on students' interest in learning physics during the pandemic. The research method used is the literature study research method. This research method is carried out by collecting relevant data from various reading sources in the form of books, journals, and other reading sources that can support researchers in solving the subject matter under study. This study indicates that the physics learning media that has been developed based on a website can increase interest in learning physics. Keywords: Learning Media, Physics, Learning Interest